Climate adaptation through farmer choice: Understanding preferences for rice varieties in coastal Bangladesh - Jaba Rani Sarker; John Rolfe; Jayanath Ananda (PLoS ONE, 2026)
The impact of environmental issues on agricultural livelihoods in Bangladesh's coastal regions—where traditional rice varieties are susceptible to salinity—is best illustrated by climate change-induced saltwater intrusion. Smallholder farmers have yet to adopt salt-tolerant rice varieties, despite the fact that they provide a technological intervention for climate adaptation. This underscores the disconnect between agricultural innovation and practical application. Farmers’ preferences for implementing these climate-resilient varieties are investigated in this study using a discrete choice experiment, which also looks at how contextual, institutional, and socio-economic factors influence technology adoption choices. Utilizing Random Parameter Logit and Latent Class Models, findings reveal three distinct farmer segments with varying willingness to pay for salt-tolerant varieties, influenced by age, savings, and land size. Post-hoc chi-square analysis reveals these preference segments are distributed evenly across districts (p = 0.822), indicating preference heterogeneity reflects individual-level differences rather than geographic salinity patterns. Each class from LCM represents the choice responses quite differently with different attributes. The majority of respondents belong to class 3 (46.5%), followed by class 1 (33.2%) and class 2 (20.3%). The largest group (46.5%) demonstrates strong preference for salt-tolerant varieties, while others prioritize different combinations of yield, profitability, and labor considerations. These results suggest that agricultural extension programs should implement differentiated strategies targeting each farmer segment, with subsidized seed distribution for resource-constrained farmers, demonstration plots for risk-averse adopters, and premium variety options for profit-oriented farmers. By highlighting the significance of context-specific approaches to promoting climate-resilient agricultural technologies and informing targeted policy interventions, these insights enable vulnerable coastal communities to achieve their broader development goals, including poverty alleviation, climate adaptation, and sustainable agricultural transformation.